2018
DOI: 10.1073/pnas.1719063115
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced transcription factor signaling is essential for larval growth of the mosquitoAedes aegypti

Abstract: Gut microbes positively affect the physiology of many animals, but the molecular mechanisms underlying these benefits remain poorly understood. We recently reported that bacteria-induced gut hypoxia functions as a signal for growth and molting of the mosquito In this study, we tested the hypothesis that transduction of a gut hypoxia signal requires hypoxia-induced transcription factors (HIFs). Expression studies showed that HIF-α was stabilized in larvae containing bacteria that induce gut hypoxia but was dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 79 publications
4
83
0
1
Order By: Relevance
“…Functional assays supporting this hypothesis include the finding that gut hypoxia activates hypoxia-induced transcription factors (HIFs) in Ae. aegypti larvae which leads to activation of the insulin/insulin growth factor pathway, select mitogen activated kinases and other processes with essential growth functions [61, 70] (Figure 1). Transcriptome analysis also identifies several genes with functions in digestion and nutrient acquisition as additional targets that are potentially regulated by the gut microbiota or microbiota-induced hypoxia [71].…”
Section: Functional Roles Of the Gut Microbiota In Mosquito Larvaementioning
confidence: 99%
“…Functional assays supporting this hypothesis include the finding that gut hypoxia activates hypoxia-induced transcription factors (HIFs) in Ae. aegypti larvae which leads to activation of the insulin/insulin growth factor pathway, select mitogen activated kinases and other processes with essential growth functions [61, 70] (Figure 1). Transcriptome analysis also identifies several genes with functions in digestion and nutrient acquisition as additional targets that are potentially regulated by the gut microbiota or microbiota-induced hypoxia [71].…”
Section: Functional Roles Of the Gut Microbiota In Mosquito Larvaementioning
confidence: 99%
“…To determine whether hypoxia-induced signalling was affected in third-instar germ-free larvae, we specifically checked the expression level of hypoxia-induced factors (HIF)-alpha and -beta (AAEL019499 and AAEL010343) and of prolyl hydroxylase (PHD)-1 and -2 genes (AAEL024908 and AAEL028025) in our samples, as HIF were reported to be induced in the presence of a microbiota in first instar larvae (Valzania et al, 2018) and are targets of PHDs. Only phd-2 was slightly down-regulated at 20h (gut: log2 fold = -1.39, padj = 0,0015; whole larvae: log2 fold = -0.6, padj = 0,015).…”
Section: Transcriptomic Analysis After Terminating Bacterial Colonisamentioning
confidence: 99%
“…Additionally, microbiota play an important role in the detoxification of noxious secondary metabolites and xenobiotics, such as terpenes, caffeine, nicotine, and insecticides, thereby enabling their insect hosts to feed on chemically defended plants . The host's physiology and behavior are often affected by microbial symbionts …”
Section: Introductionmentioning
confidence: 99%
“…6 The host's physiology and behavior are often affected by microbial symbionts. 14,15 Previous studies indicated that the structure of insect bacterial communities can be shaped by multiple endogenous and exogenous factors, such as host phylogeny, environment, and diet. [16][17][18] The gut bacterial diversity of termites and cockroaches revealed that host phylogeny was an important factor that determined gut microbial composition.…”
Section: Introductionmentioning
confidence: 99%